2021
DOI: 10.1055/s-0041-1731777
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Appropriate Dosing of Nonvitamin K Antagonist Oral Anticoagulants for Stroke Prevention in Patients with Atrial Fibrillation

Abstract: Preventing thromboembolic events, while minimizing bleeding risks, remains challenging when managing patients with atrial fibrillation (AF). Several factors contribute to current dosing patterns of nonvitamin K antagonist oral anticoagulants (NOACs), including patient characteristics, comorbidities, and physician judgment. Application of NOAC doses inconsistent with the drug labels may cause patients to receive either subtherapeutic (increasing stroke risk) or supratherapeutic (increasing bleeding risk) antico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
(117 reference statements)
0
5
1
Order By: Relevance
“…Our findings differed from those in studies from the United States (US), 14–16 Europe, 17–21 Israel, 22 and Asia 23–28 reporting the association between reduced-dose DOACs and the increased risk of S/SE. Some systematic reviews have also reported that use of reduced-dose DOACs produced less favorable outcomes than standard-dose DOACs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings differed from those in studies from the United States (US), 14–16 Europe, 17–21 Israel, 22 and Asia 23–28 reporting the association between reduced-dose DOACs and the increased risk of S/SE. Some systematic reviews have also reported that use of reduced-dose DOACs produced less favorable outcomes than standard-dose DOACs.…”
Section: Discussioncontrasting
confidence: 99%
“…Some systematic reviews have also reported that use of reduced-dose DOACs produced less favorable outcomes than standard-dose DOACs. 17 , 29–32 However, several reports, mainly from Asia 33–46 but also from the US 47–50 and Israel, 51 as well as international/global studies, 52 , 53 show that reduced-dose DOACs were not associated with an increased risk of S/SE; in some of these studies, investigators specified reduced-dose as “inappropriately reduced-dose” or “off-label underdose”. 39 , 47–49 , 51 , 53 In a recent systematic review, Choi et al reported that reduced-dose DOACs were not associated with an increased risk of S/SE in Asians, 54 and Shen et al reported the same conclusion in a systematic review that included a diverse population.…”
Section: Discussionmentioning
confidence: 99%
“…One is that physicians correctly take more clinical factors into consideration and hence, both the SmPC and EHRA PG still fall short of guide clinical practice. However, prior retrospective and observational data have clearly shown that dosing that deviates from recommendations is associated with increased risk of adverse events and even mortality [ 7 , 27 ]. Therefore, the second explanation is that physicians still are falling short of making correct dosing decisions, which calls for more physician education to improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Doctors must not choose lower dose of NOACs just out of a fear of bleeding (thus ignoring the risk of stroke) [74]. Under-dosing of NOACs in patients with AF may be associated with reduced effectiveness for stroke prevention, with similar or even increased bleeding than with the standard dose [81]. Anticoagulation monitoring enables personalized and…”
Section: Underdosingmentioning
confidence: 99%